2017
DOI: 10.1016/j.jaci.2016.09.056
|View full text |Cite
|
Sign up to set email alerts
|

Effect of probiotics in prevention of atopic dermatitis is dependent on the intrinsic microbiota at early infancy

Abstract: Disclosure of potential conflict of interest: T. Øien has received a grant and travel support from Tine BA. C. K. Dotterud has received a grant from Tine BA. K. Rudi has a board membership with Genetic Analysis AS; receives royalties from Nofima AS and Invent2, UiO; and owns stock in Genetic Analysis AS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 14 publications
3
28
0
1
Order By: Relevance
“…Similarly, children born to mothers receiving probiotic supplementation during pregnancy, compared with control, showed a 40% reduction in atopic dermatitis. More interestingly, atopic children within the treatment group had significantly higher levels of Bifidobacterium dentium compared with healthy children, as early as 10 d, indicating a differential outcome based on early colonizers of the gut (131). This is consistent with the hypothesis that mothers pass microbes on to their children in the womb (132) and the transmission of maternal microbes may be modifiable (133,134).…”
Section: Maternal Environment and The Infant Microbiomesupporting
confidence: 77%
“…Similarly, children born to mothers receiving probiotic supplementation during pregnancy, compared with control, showed a 40% reduction in atopic dermatitis. More interestingly, atopic children within the treatment group had significantly higher levels of Bifidobacterium dentium compared with healthy children, as early as 10 d, indicating a differential outcome based on early colonizers of the gut (131). This is consistent with the hypothesis that mothers pass microbes on to their children in the womb (132) and the transmission of maternal microbes may be modifiable (133,134).…”
Section: Maternal Environment and The Infant Microbiomesupporting
confidence: 77%
“…A factor that may contribute to this lack of coherent results is differences in the composition and function of gut microbiota. This has been illustrated for probiotic application by our recent study showing that the effect of probiotics on prevention of atopic dermatitis is associated with the intrinsic microbiota in early infancy [108]. …”
Section: Personalized Use Of Probiotics and Prebioticsmentioning
confidence: 99%
“…As some children with AD had high levels of Th22 despite being in the probiotic group, one can speculate whether the preventive effect of probiotics was restricted to specific populations. Our group has recently reported that the effect of probiotics in the prevention of AD can be dependent on the intrinsic microbiota . High levels of Bifidobacterium dentium were associated with lack of the probiotic effect.…”
Section: Discussionmentioning
confidence: 98%